A Current and Future Perspective on Adjuvant and Neoadjuvant Recirculating Chemohyperthermia as a Treatment for Intermediate-High Risk NMIBC - Leon-Mata, Juan; Sousa-Gonzalez, Daniel; Alvarez-Casal, Maria; Flores-Carbajal, Javier; Sousa-Escandón, Alejandro (Current Overview on Disease and Health Research Vol. 2, 2022)
Non-muscle invasive bladder cancer (NMIBC) accounts for around 75% of all bladder cancer diagnoses, with more than half of them relapsing following transurethral resection of the bladder tumour. Adjuvant intravesical chemotherapy with mitomycin C (MMC) and immunotherapy with bacillus Calmette-Guérin (BCG) are traditionally used to prevent recurrences. Unfortunately, many patients relapse after getting these treatments, and a large percentage of them will require surgery. T1G3 tumours had a risk of advancement of over 19 percent after one to three years of BCG maintenance. To improve the effectiveness of adjuvant intravesical therapy, many innovative treatment techniques are being researched. Chemohyperthermia (CHT), a combination of intravesical chemotherapy and hyperthermia, is one of the newer treatments for intermediate and high-risk NMIBC. The objective of this article is to review the mechanism of action, current status and indications, results and future perspectives of recirculating chemohyperthermia as a treatment for intermediate-high risk NMIBC.